Implementation of the adverse childhood experiences conversation in primary care. (23rd November 2019) - Bodendorfer, Victoria; Koball, Afton M; Rasmussen, Cary; Klevan, Judy; Ramirez, Luis; Olson-Dorff, Denyse
Abstract: Background: Research has focused on screening for adverse childhood experiences, rather than provision of education as a part of routine anticipatory guidance. An adverse childhood experiences 'conversation' is one method that has not been studied empirically but represents a complimentary or alternative approach to screening which could overcome many existing barriers. Objectives: This study aims to examine parent/guardian and provider acceptability/feasibility of the adverse childhood experiences conversation during well-child visits in primary care. Methods: Providers engaged in a conversation with parents/guardians of patients during well-child visits in a family medicine residency clinic. Parents/guardians and providers were surveyed following the visit to examine acceptability and feasibility. Quarterly assessments to further examine provider perspectives were completed. Data were collected for 1 year. Results: In total, 238 parent/guardian and 231 provider surveys were completed. Most parents/guardians felt positively (76%) about and comfortable (81%) with the information discussed and 97% felt that the conversation should be had with their primary care provider specifically. Most providers (71%) indicated that parents/guardians were receptive to the conversation, that the conversations took 1–2 minutes (60%) and that there were few disclosures of adversity (9%), none of which required mandatory reporting. Conclusions: Results suggest that the adverse childhood experiences conversation is well received by parents/guardians and providers and is feasible to implement into primary care. The conversation could be used as a complimentary or alternative method to screening to further spread knowledge of toxic stress and health, provide resources for families and promote resilience.